Upaya Meningkatkan Hasil Belajar IPA Materi Energi dan Perubahannya dengan Menggunakan Metode Proyek pada Siswa Kelas VI SD Negeri 01 Tanjuang Balik Kecamatan Pangkalan Koto Baru - Refnalti Refnalti (Eduscience Development Journal, 2019)
Science learning class VI in SD Negeri 01 Tanjuang Balik Kec. Pangkalan Koto Baru has not used a variety of active learning methods and is still not appropriate, this causes students to tend to be passive and the lack of teaching methods on the material delivered by the teacher especially the energy material and its changes. This is evidenced by the low learning outcomes of students who have not yet reached KKM 75. The formulation of the problem of this study is whether the Project Method can improve the learning outcomes of the Energy Science material and its Changes in Grade VI students at SD Negeri 01 Tanjuang Balik Kec. Poto Baru Base ?. The purpose of this study was to determine the Project Method to improve the learning outcomes of the Science of Energy and its material changes in Grade VI at SD Negeri 01 Tanjuang Balik Kec. Koto Baru Base. This research is a classroom action research conducted in three cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. The subjects of the study were the sixth grade students at SD Negeri 01 Tanjuang Balik Kec. Pangkalan Koto Baru, which has 29 students, includes 14 male students and 15 female students. Assessment instruments include lesson plans, teacher observation sheets, teacher and student observation sheets, and evaluation tests. Data collection methods used are interviews, observation, documentation, and tests. Descriptive data analysis techniques using the percentage formula, if ≥ 85% of students complete learning the cycle is stopped. The results showed that the project learning method could improve the learning outcomes of the Science of Energy and its material changes in Grade VI students of SD Negeri 01 Tanjuang Balik Kec. Koto Baru Base. The average student learning outcomes increase in each cycle, in the pre cycle the average student learning outcomes reached 66.21, the first cycle the average student learning outcomes reached 73.10, the second cycle the average student learning reached 83.10 and cycle III the average student learning reaches 90.34. The results showed that the project learning method could improve the learning outcomes of the Science of Energy and its material changes in Grade VI students of SD Negeri 01 Tanjuang Balik, Pangkalan Koto Baru District. Increased mastery learning with KKM 75 pre cycle there were 6 students (20.69%) completed learning and 23 students (79.31%) did not complete study. Cycle I obtained data on 12 students (41.38%) completing learning and 17 students (58.62%) not completing learning. Cycle II, there were 21 students (72.41%) completing learning and 8 students (27.59%) not completing learning. Cycle III there are 29 students (100%) completed learning and 0 students (0%) did not complete study. The results of these data can be seen that the value of student learning outcomes from pre-cycle to cycle III has increased. The implementation of learning in cycle III has met the established learning completeness criteria that is ≥ 75% of the total number of students who have finished learning, because what is achieved is the maximum value so that classroom action research is stopped in this third cycle.